Convection, but How Fast Does Fluid Mix in Hydrothermal Systems? - H. N. Ulloa; D. Noto; J. A. Letelier (Geophysical Research Letters)
Abstract The destabilizing thermal gradient across the Earth's lithosphere drives convection in superconfined hydrothermal environments at mid‐ocean ridges and geothermal reservoirs in the continental crust. Deep, hot waters rise in these regions and meet cold surface water that percolates through open fractures, creating complex and poorly understood mixing dynamics. This Letter explores the relationship between energy, convection, and mixing in analog hydrothermal systems. Leveraging energetics theory and lab‐scale experiments, we present a scaling formulation for estimating the irreversible mixing boosted by convective flows occurring within faulted and fractured hydrothermal environments. These findings bear relevance to natural Earth processes and human‐engineered applications, such as geothermal energy harvesting and geologic CO2 sequestration.